2021
DOI: 10.7759/cureus.17967
|View full text |Cite
|
Sign up to set email alerts
|

Primary Spontaneous Inferior Clival Cerebrospinal Fluid Leak

Abstract: Primary, spontaneous cerebrospinal fluid (CSF) leaks secondary to defects in the clivus are exceedingly rare. Additionally, primary, spontaneous CSF leaks are typically present in obese women with idiopathic intracranial hypertension (IIH). In the present study, we report the first case of a primary, spontaneous CSF leak in the inferior-posterior wall of the clivus in an atypical patient with a BMI of 18.9 kg/m 2 without IIH. Accurate diagnoses of CSF leaks are imperative in the context of preventing meningiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…For skull base reconstructions due to spontaneous CSF leakage at the clivus, previous studies have reported harvesting autografts and conducting a multilayered reconstruction (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, these techniques require invasive procedures outside the main surgical site, i.e., the endonasal area, to harvest the reconstructive material.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For skull base reconstructions due to spontaneous CSF leakage at the clivus, previous studies have reported harvesting autografts and conducting a multilayered reconstruction (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, these techniques require invasive procedures outside the main surgical site, i.e., the endonasal area, to harvest the reconstructive material.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the diagnosis of this condition, half of these patients have a history of meningitis before the diagnosis of CSF leakage [1][2][3][4][5][6][8][9][10][11][12], and all have serous rhinorrhea [1][2][3][4][5][6][7][8][9][11][12][13]. This is a characteristic course of the condition but may be overlooked because of the rarity of the condition itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations